2016
DOI: 10.1016/j.prevetmed.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Circulating serovars of Leptospira in cart horses of central and southern Ethiopia and associated risk factors

Abstract: Little work has been done on diseases of horses in Ethiopia or tropical regions of the world.Yet, Ethiopia has the largest horse population in Africa and their horses play a pivotal role in their economy as traction animals. A serological and questionnaire survey was therefore conducted to determine the circulating serovars of Leptospira and their association with potential risk factors in the cart horse population of Central and Southern Ethiopia. A total of 184 out of 418 cart horses from 13 districts had an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
2
14
0
2
Order By: Relevance
“…The presence of pest control measures significantly reduced the chance for Bardigiano horses getting the infection. Although the role of rodents in transmission of leptospiral serovars can sometimes be difficult to evaluate [31], rodent control is considered an important factor for prevention [6,34] and our data confirm this notion. In this study, the presence of other domestic animals did not significantly affect the seroprevalence.…”
Section: Discussionsupporting
confidence: 83%
“…The presence of pest control measures significantly reduced the chance for Bardigiano horses getting the infection. Although the role of rodents in transmission of leptospiral serovars can sometimes be difficult to evaluate [31], rodent control is considered an important factor for prevention [6,34] and our data confirm this notion. In this study, the presence of other domestic animals did not significantly affect the seroprevalence.…”
Section: Discussionsupporting
confidence: 83%
“…Risk factors for clinical disease that have been described for people and dogs include contact with outdoor water sources as might occur with swimming in and consumption of outdoor water sources. Risk factors for clinical disease in horses have not been described, but seropositivity was associated with geographic location, increased age, drinking of river water and the presence of dogs in the adjacent properties in horses in Ethiopia . Another study identified exposure to rodents and wildlife among other factors to be associated with seropositivity in horses…”
Section: Discussionmentioning
confidence: 55%
“…Risk factors for clinical disease in horses have not been described, but seropositivity was associated with geographic location, increased age, drinking of river water and the presence of dogs in the adjacent properties in horses in Ethiopia. 21 Another study identified exposure to rodents and wildlife among other factors to be associated with seropositivity in horses. 22 The foals described here were of the same age, showed similar clinical signs, and all of the animals survived to discharge.…”
Section: Discussionmentioning
confidence: 61%
“…Titres of various serovars have been reported in horses, but Icterohaemorrhagiae, Bratislava, Copenhageni, and Pomona are among the most prevalent serovars (27). Pakistan is a tropical country (22) and in tropical regions serogroup Icterohaemorrhagiae has been reported to be the most frequent infection (3).…”
Section: Discussionmentioning
confidence: 99%